In vitro propagation of virus-free yacon (Smallanthus sonchifolius) - YANG Xu; JIANG Wei-mei; DING Bing-yang (浙江大学学报. 农业与生命科学版)
The virus-free yacon was got by culturing the meristem-tip from axillary buds of its tuber. The cucumber mosaic virus (CMV) was detected by DAS-ELISA. The results showed that 0.3 mm meristem-tip culture was an effective means for virus elimination and the ratio of virus elimination amount to 60%. A reliable and reproducible method for plant regeneration of yacon was developed which utilizes the stem (with nodes) and leaves from the virus-free plantlet as explants. The optimal proliferating shoot cultures medium from stems was MS supplemented with BAP 1 mg·L-1 and NAA 0.1 mg·L-1. Highly regenerative callus was obtained from the leaves following cultivation on MS medium supplemented with BA 0.2 mg·L-1, TDZ 0.01 mg·L-1 and NAA 0.05 mg·L-1. Regenerated shoots could produce roots in 1/2MS medium containing NAA 0.01 mg·L-1 and the plantlets were successfully transferred to soil, the survival rate being up to 80%.